The effect of resveratrol supplementation on the expression levels of factors associated with cellular senescence and sCD163/sTWEAK ratio in patients with type 2 diabetes mellitus: study protocol for a double-blind controlled randomised clinical trial - Shima Abdollahi; Amin Salehi-Abargouei; Mahtab Tabatabaie; Mohammad Hasan Sheikhha; Hossein Fallahzadeh; Masoud Rahmanian; Omid Toupchian; Elham Karimi-Nazari; Hassan Mozaffari-Khosravi (BMJ Open)
Introduction Over the past decades, the number of people with type 2 diabetes (T2D) has increased globally. One of the major complications in these patients is cardiovascular disease; it seems that the cell proliferation inhibition can improve vascular function in these patients. It is proposed that peroxisome proliferator-activated receptor alpha (PPARα) can induce cell cycle arrest via cyclin-dependent kinase inhibitor 2A (p16) activation. Also, it has been shown that phosphorylated tumour suppressor protein p53 is involved in cell senescence by cyclin-dependent kinase inhibitor 1 (p21) upregulation. Resveratrol is a natural polyphenol and appears to improve the vascular function through the mentioned pathways. We will aim to evaluate the effects of resveratrol supplementation on mRNA expression of PPARα, p53, p21 and p16 in patients with T2D. We will also measure serum levels of cluster of differentiation 163 (CD163) and tumour necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) as the indicators of cardiovascular status.Methods and analysis Seventy-two subjects suffering from T2D will participate in this double-blind randomised parallel placebo-controlled clinical trial. Participants will be randomly assigned to receive 1000 mg/day trans-resveratrol or placebo (methyl cellulose) for 8 weeks. The mRNA expression levels of PPARα, p53, p21 and p16 genes will be assessed using real-time PCR and serum CD163 and TWEAK levels will be measured using commercially available ELISA kits at baseline and the end of the study. Clinical outcome parameters (glycaemic and lipid profiles and body composition) will also be measured before and after study duration.Ethics and dissemination The study is performed in agreement with the Declaration of Helsinki and is approved by the Ethics Committee of the Shahid Sadoughi University of Medical Sciences (no: ir.ssu.sph.rec.1396.120). The results will be published in scientific journals.Trial registration number IRCT20171118037528N1; Pre-results.